2018
DOI: 10.1108/lhtn-11-2017-0083
|View full text |Cite
|
Sign up to set email alerts
|

Android based voice assistant for blind people

Abstract: Purpose The purpose of this study is to discuss the development of Android-based Intelligent Software Assistant application for visually challenged or blind people. The application is intended to help people with visual limitations or blind people to access Android-based devices so that they can use library resources by using android devices. Design/methodology/approach The necessary data are collected from journals, articles, books and questionnaires, and similar applications are analyzed. The application d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Text-based conversational agents have been extensively studied in the domain of digital health interventions [ 80 - 83 ] and can be considered as a precursor to VCAs [ 9 ]. Moreover, voice modality may differ in their appropriateness of app, compared with text modality, depending on the health-related context (eg, public spaces [ 84 , 85 ] and type of user [ 24 - 26 , 86 , 87 ]). Thus, future research should not only standardize the research in terms of implementation and evaluation measures but also consistently evaluate this technology against what we could consider the gold standard of conversational agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Text-based conversational agents have been extensively studied in the domain of digital health interventions [ 80 - 83 ] and can be considered as a precursor to VCAs [ 9 ]. Moreover, voice modality may differ in their appropriateness of app, compared with text modality, depending on the health-related context (eg, public spaces [ 84 , 85 ] and type of user [ 24 - 26 , 86 , 87 ]). Thus, future research should not only standardize the research in terms of implementation and evaluation measures but also consistently evaluate this technology against what we could consider the gold standard of conversational agents.…”
Section: Discussionmentioning
confidence: 99%
“…First, voice-based interaction leverages the naturalness [ 20 , 21 ] and social presence [ 22 , 23 ] of human-to-human conversation. Second, it facilitates input for users with low literacy or with visual [ 24 ], intellectual [ 25 ], motor, linguistic, and cognitive disabilities [ 26 ] and can support more natural health routine tasks when in-person health care is not possible [ 19 , 27 ]. Third, it opens the door to voice or speech analysis, whereas features of the patient’s utterances can be passively monitored to derive health states [ 28 - 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, VAs leverage speech-based interaction, which makes information lookup more efficient and accessible compared to classical methods (eg, desktop web search [11,12]). This is particularly the case in situations in which users have their hands occupied [13][14][15][16][17], lack reading and writing skills [18], or suffer from visual, motor, or cognitive inabilities [19][20][21][22][23][24] and cannot access information on display devices, such as smartphones, desktops, or tablets. Hence, VAs are a powerful alternative to provide chronic patients with easy access to information about NCD management.…”
Section: Voice Assistants For Information Lookupmentioning
confidence: 99%
“…Therefore, the total number of voice assistance users is growing steadily. Moreover, new consumer groups such as blind people (Barata et al 2018) and children (Lovato and Piper 2019) are using these services with rising demand, whereby children are socialized at an early age to use them. A Swiss study showed that one-third of the Swiss population is already using voice functions mainly via smartphone (Kunath et al 2019).…”
Section: Introductionmentioning
confidence: 99%